Cognitive Process of Psoriasis and Its Comorbidities: From Epidemiology to Genetics - Gao, Jing; Shen, Xue; Ko, Randy; Huang, Cong; Shen, Changbing (Frontiers in Genetics, 2021)
Psoriasis (PsO) is a chronic inflammatory skin disease that affects approximately 2% people all over the world. PsO comorbidities have increasingly become more of interest in the past decades. Compared with the normal population, the incidences of comorbidities are higher among patients with PsO. In the last twenty years, researchers have focused on studying the genetic components of PsO and genetic associations between PsO and its comorbidities were elucidated. This review provides an in-depth understanding and summarization of the connection between PsO and its comorbidities from the perspectives of epidemiology and genetics. Further understanding of PsO and its comorbidities will promote research on the pathogenesis, drug development, novel therapy methods, personalized and precision treatment of PsO and its comorbidities.